2010
DOI: 10.1007/s00066-010-2090-9
|View full text |Cite
|
Sign up to set email alerts
|

Nodal Follicular Lymphoma

Abstract: Since there is no evidence so far that the prognosis of stage I and II nodal FL can be improved by the use of EFI/TNI/TLI, IFI is recommended internationally. Adequate irradiation doses range between 25-30 Gy to subclinical disease and 36-40 Gy to involved sites. To further improve the curative potential of RT in early-stage FL, novel combined approaches (e.g., RT + immunotherapy with rituximab) are under investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 58 publications
2
6
0
Order By: Relevance
“…Our PFS of 54% and OS of 59% at 10 years and 92% local control are consistent with previous radiation-only series published within the last 15 years [5], [6], [9], [15][26]. In these series stage I and II FL treated with RT alone produces PFS of 30–50%, OS of 60–70% at 10 years and local control in the range of 90–95%.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Our PFS of 54% and OS of 59% at 10 years and 92% local control are consistent with previous radiation-only series published within the last 15 years [5], [6], [9], [15][26]. In these series stage I and II FL treated with RT alone produces PFS of 30–50%, OS of 60–70% at 10 years and local control in the range of 90–95%.…”
Section: Discussionsupporting
confidence: 91%
“…Observation alone is a reasonable option when potential toxicity from radiation out weighs its benefit because of the extent and location of the disease [4]. In the pre-rituximab era chemotherapy had not been convincingly shown to improve treatment results compared to radiation alone [5]. An analysis of 144 stage 1 (by bone marrow) FL patients grade I–II enrolled in the National Lymphocare data base with a median follow up of 57 months reported that patients who received either rituximab and chemotherapy (R-chemo) or R-chemo plus radiotherapy had significantly improved PFS but no difference in OS compared with patients receiving radiotherapy alone.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The observed OS is in good agreement with published data in the literature about primary radiotherapy for stages I/II follicular lymphoma: two recent literature reviews reported 10-years OS rates ranging between 46% and 79% (weighted average of 63% in Heinzelmann et al) after primary radiotherapy using mostly IFI or EFI [11,12]. No obvious correlation of OS and irradiated volume is seen in this literature review.…”
Section: Discussionsupporting
confidence: 91%
“…They are commonly diagnosed in localized stages (Ann-Arbor stage I and II) and stay localized for a long time. Previous studies have shown excellent outcomes after radiotherapy in treatment of MALT lymphoma as an organ-preserving treatment modality [3] as has also been shown for other indolent lymphoma subtypes [4]. We report the outcomes of a retrospective analysis of 30 patients with stage I-II MALT-lymphoma treated with radiotherapy at our Institution.…”
Section: Introductionmentioning
confidence: 87%